Asupan Zat Besi (Fe) dan Vitamin C dengan Status Anemia Gizi Besi pada Ibu Hamil di Kelurahan Tuatunu Pangkalpinang - Ade Devriany; Zenderi Wardani; Marwan Marwan (Jurnal Kesehatan Manarang, 2018)
Based Health Research (2013) reported that the prevalence of anemia in pregnant women in Indonesia about 37.1%. Iron Deficiency Anemia is a health problem associated with a high incidence and complications that may arise on the mother and fetus. The aims of this study was to determine the correlation between the intake of iron (Fe) and vitamin C with iron deficiency anemia for pregnant women in Tua Tunu, Gerunggang, Pangkalpinang in 2015. This type of research was descriptive analytic study with cross sectional design. The total samples were 30 pregnant women. Measurement of hemoglobin was done by using the Easy Touch GcHb. The intake of iron (Fe) and vitamin C obtained by the method of 24-hour food recall for 5 times on days that are not consecutive. The correlation intake of iron (Fe) and vitamin C with iron deficiency anemia status were analyzed by Pearson product moment. These results indicate that 86.7% of pregnant women were inadequate intake of iron (Fe) and there were 80% of pregnant women inadequate for vitamin C. The number of pregnant women had iron deficiency anemia about 56.7%. The results of the analysis showed that there was a significant correlation between the intake of iron (Fe) and vitamin C with iron deficiency anemia status (p value = 0.000). Based on these results, it is recommended to pregnant women to do improvement for intake of iron and vitamins C and for the prevention of iron deficiency anemia problem needs to do Monitoring for Drug Intake and the provision of Multiple Micronutrient (MM).